Differences in The Effect of Breast Care and Oketani Massage on Breast Milk Production in Postpartum Mothers - Adzillina Alal Mukminin, Siti; Maharrani, Titi; Isfentiani, Dina; Nurwulansari, Fitria (Universitas Nahdlatul Ulama Surabaya, 2025)
The low breastfeeding coverage is proven by the high rate of infant stunting in Indonesia. Apart from inadequate implementation of breast care, maternal diet, and psychology also play a role in the limited coverage of exclusive breastfeeding. This research aimed to determine the mother's ability to produce breast milk after breast care and Oketani massage. Dupak Community Health Center was the research location, and a quasi-experimental nonrandomized control group pretest-posttest design was used. Thirty-two postpartum mothers were selected using purposive sampling. Breast milk production observation sheet as a research instrument. Data analysis with Wilcoxon and Mann Withney U. Results: The Mann Withney U test revealed no difference in the effect of breast care and massage on postpartum mothers' ability to produce breast milk, with a p-value of 0.093, meaning that H0 is accepted and H1 is rejected. The Wilcoxon test revealed that postpartum mothers' ability to produce breast milk was influenced by breast care and massage, with a p-value of 0.001. Conclusion: There is no real difference between the effects of Oketani massage and breast care on breast milk supply. It is recommended that more researchers develop new intervention strategies by including characteristics that influence postnatal mothers' ability to produce breast milk